ANALISIS TEGANGAN EKUIVALEN FENDER BENTUK SETENGAH PIPA DAN BENTUK PELAT H PADA KAPAL MENGGUNAKAN METODE ELEMEN HINGGA: Analysis of Equivalent Stress on Half-Pipe and H-Plate Shaped Fenders on Ships using Finite Element Method - Firmansyah , Ainun; Priyambodo Nur Ardi Nugroho; Wulandari, Dyah Arum (Universitas Negeri Jakarta, 2023)
Fenders are structures installed on the edges of ships to protect the ship's hull from impact with the dock. The main function of fenders is to absorb the collision energy generated by the ship's impact during berthing at a dock. The load applied to fenders on each ship results in stress distribution in the surrounding hull area, which can lead to various issues such as damage, cracks, deformations, and others. Additionally, the presence of fenders with different shapes can affect the stress distribution values in the surrounding hull area. Hence, a local stress analysis using finite element method software is necessary. The analysis focuses on static loads originating from the ship itself when docked at a port. However, only the fender section is analyzed, and it is not necessary to consider the entire ship's body. The objective of the analysis is to determine the stress characteristics and maximum stress values in the fender itself. The analysis results reveal that the highest stress value occurs in the half-pipe-shaped fender with a value of 0.22809 MPa. Based on these findings, it can be concluded that the stress values in the fender meet the allowable standards. In conclusion, this analysis provides an understanding of stress and the maximum stress value in ship fenders. This knowledge is crucial to ensure that fenders effectively fulfill their function of protecting the ship from impacts with docks.